Public Accountability in Financial Management Practice at Islamic Education Institutions: A Survey Research - Akhyar, Yundri (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study examines the financial management practices of Islamic educational institutions, with a focus on public accountability. As financial transparency and accountability become increasingly important in educational organizations, it is essential to evaluate how Islamic institutions manage their financial resources. A survey research design was employed to assess perceptions of financial management accountability. Data were collected using a questionnaire distributed via Google Forms, with a sample size of 162 participants from various Islamic education institutions. The findings revealed that respondents generally hold positive views regarding the transparency of financial management practices at Islamic educational institutions. However, challenges in implementing these practices were also identified, such as limited financial training, technological infrastructure gaps, and insufficient stakeholder engagement. While the positive perception of transparency indicates a solid foundation for accountable financial management, the study highlights the need for further improvements. Recommendations include enhancing financial training, upgrading technology, increasing stakeholder involvement, and conducting regular financial audits. Additionally, institutions are encouraged to benchmark their practices against industry best standards to ensure ethical and efficient resource utilization. This research underscores the importance of fostering a culture of accountability in financial management within Islamic educational institutions. By addressing identified challenges and adopting the suggested improvements, these institutions can better ensure financial transparency and ethical resource management.